Berlin Alexanderplatz - Döblin, Alfred, 1878-1957 (New York Review Books classics, 2018)
"The inspiration for Rainer Werner Fassbinder's epic film and that The Guardian named one of the "Top 100 Books of All Time," Berlin Alexanderplatz is considered one of the most important works of the Weimar Republic and twentieth century literature. Franz Biberkopf, pimp and petty thief, has just finished serving a term in prison for murdering his girlfriend. He's on his own in Weimar Berlin with its lousy economy and frontier morality, but Franz is determined to turn over new leaf, get ahead, make an honest man of himself, and so on and so forth. He hawks papers, chases girls, needs and bleeds money, gets mixed up in spite of himself in various criminal and political schemes, and when he tries to back out of them, it's at the cost of an arm. This is only the beginning of our modern everyman's multiplying misfortunes, but though Franz is more dupe than hustler, in the end, well, persistence is rewarded and things might be said to work out. Just like in a novel. Lucky Franz.Berlin, Alexanderplatz is one of great twentieth-century novels. Taking off from the work of Dos Passos and Joyce, Doblin depicts modern life in all its shocking violence, corruption, splendor, and horror. Michael Hofmann, celebrated for his translations of Joseph Roth and Franz Kafka, has prepared a new version, the first in over 75 years, in which Doblin's sublime and scurrilous masterpiece comes alive in English as never before"--